Inovasi Pengelolaan Limbah Organik Rumah Tangga: Pembuatan Ekoenzim (EE) di Desa Luthu Lamweu, Kecamatan Sukamakmur, Kabupaten Aceh Besar - Kamaruzzaman, Suraiya; Hisbullah, Hisbullah; Ambarita, Aulia Chintia; Sy, Yuliana; Mukhriza, Teuku; Nasution, Fahrizal (Universitas Syiah Kuala, 2024)
Transforming household organic waste (such as leftover food, fruits, vegetables, and other organic materials) into eco-enzymes represents a pioneering community service initiative in Luthu Lamweu Village, Sukamakmur District, Aceh Besar, Aceh Province, Indonesia. This project aims to enhance environmental awareness and improve community welfare. The villagers of Luthu Lamweu possess significant potential in converting organic waste into valuable products. The research methodology employed a participatory approach, actively engaging the community in all stages, including awareness campaigns (socialization), training sessions, technical support for eco-enzyme production, and evaluation. The strategy involved collaboration with village authorities, facilitated through the Program Bakti Mahasiswa Teknik (PBMT) and lecturer-led community service (PkM) to ensure program sustainability. The community service outcomes indicated a substantial increase in the communitys knowledge, interest, and skills in managing household organic waste into eco-enzymes, with a success rate of 96.25% (rated from sufficient to very good). Furthermore, the program positively impacted the villages environmental quality by converting organic waste into valuable eco-enzymes.